Association of androgen deprivation therapy with thromboembolic events in patients with prostate cancer: a systematic review and meta-analysis. Issue 4 (November 2018) - Guo, Zhenlang; Huang, Yiyu; Gong, Leiliang; Gan, Shu; Chan, Franky; Gu, Chiming; Xiang, Songtao; Wang, Shusheng
Abstract Background: Whether androgen deprivation therapy (ADT) causes excess thromboembolic events (TEs) in men with prostate cancer (PCa) remains controversial and is the subject of the US Food and Drug Administration safety warning. This study aims to perform a systematic review and meta-analysis on previous studies to determine whether ADT is associated with TEs in men with PCa. Methods: Medline, Embase, and Cochrane Library databases were searched for relevant studies. These studies comprised those that compared ADT versus control to treat PCa, reported TEs as outcome, and were published before January 2018. Multivariate adjusted hazard ratios (HRs) and associated 95% confidence intervals (CIs) were calculated using random- or fixed-effects models. Results: Five retrospective population-based cohort studies involving 170, 851 ADT users and 256, 704 non-ADT users were identified. Deep venous thrombosis (DVT) was found significantly associated with gonadotropin-releasing hormone (GnRH) agonists alone (HR = 1.47, 95% CI: 1.07–2.03;P  = 0.017;I 2  = 96.3%), GnRH agonists plus oral antiandrogen (AA) (HR = 2.55, 95% CI: 2.21–2.94;P  < 0.001;I 2  = 0.0%), and AA alone (HR = 1.49, 95% CI: 1.13–1.96;P  = 0.004;I 2  = 0.0%), but not with orchiectomy (HR = 1.80, 95% CI: 0.93–3.47;P  = 0.079;I 2  = 94.8%). In addition, pulmonary embolism (PE) was significantly associated with GnRH agonists alone (HR = 2.26, 95% CI: 1.78–2.86;P  < 0.001;I 2 was unavailable) and orchiectomy (HR = 2.12, 95% CI: 1.44–3.11;P  < 0.001;I 2  = 57.2%). This relationship was also supported with subgroup analyses based on different continents and races. Conclusions: GnRH agonists alone, GnRH plus AA, and AA alone cause excess DVT in men with PCa after controlling the demographic and disease characteristics and other confounding factors, although statistically significant difference was not observed in orchiectomy group. Additionally, GnRH agonists alone and orchiectomy can increase the incidence of PE.